The effect of nanoparticle additive on surface milling in glass fiber reinforced composite structures. Issue 9 (November 2021) - Ceritbinmez, Ferhat; Yapici, Ahmet; Kanca, Erdoğan
In this study, the effect of adding nanosize additive to glass fiber reinforced composite plates on mechanical properties and surface milling was investigated. In the light of the investigations, with the addition of MWCNTs additive in the composite production, the strength of the material has been changed and the more durable composite materials have been obtained. Slots were opened with different cutting speed and feed rate parameters to the composite layers. Surface roughness of the composite layers and slot size were examined and also abrasions of cutting tools used in cutting process were determined. It was observed that the addition of nanoparticles to the laminated glass fiber composite materials played an effective role in the strength of the material and caused cutting tool wear.